Isixhosa interpretations of the Nongqawuse saga: oral narratives and theatrical performances of the Nongqawuse story - Yani, Sikhumbuzo (School of Languages and Literatures, 2019)
The subject of this thesis is centred on the creative and linguistic interpretations (in English and isiXhosa) of the Nongqawuse prophecy and the cattle-killing of 1856-1857. By examining a range of historical, cultural and anthropological sources, the study foregrounds traditional African theatre elements as well as language as being important to a fresh understanding and appreciation of the Nongqawuse story. Using textual analysis as a methodological choice, the study analyses H.I.E Dhlomo’s The Girl Who Killed to Save, Xolani Mkonko’s Nongqawuse: a dissertation of true lies and Brett Bailey’s The Prophet to locate the linguistic construct of the plays as well as their theatrical and performative aesthetics. The study adopts the Afrocentric theory in order to interrogate the texts within a decolonial context and locates the Nongqawuse prophecy and the eventual cattle killing as a narrative that communicates the traditional, cultural, historical and spiritual universe that defines amaXhosa of South Africa. While taking as its subject an event from more than 150 years ago, and literary debates from shortly after, my study has been able to contribute robustly to wider conversations that relate to the Nongqawuse prophecy and cattle killing and how the history is reshaped by African voices in terms of language and performance tradition. Added to this, the study contributes to the field of African languages by critiquing how these dramatic works, which focus on Nongqawuse’s prophecy, creatively and refreshingly are inspired by Xhosa genres of orature and storytelling, set within a period of great upheaval due to missionary and colonial influences.